PRIMARY EDUCATION CURRICULUM DEVELOPMENT: EFFORTS TO REALISE ACTIVE AND FUN LEARNING - Aslan Aslan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Primary education curriculum development is a strategic effort to improve the quality of learning at the primary level. A good curriculum is able to answer the challenges of the times and the needs of students by making the learning process active and fun. This article discusses current approaches to curriculum development in primary education, such as thematic, integrative and the use of educational technology. The research focuses on how implementing a curriculum designed with these methods can improve student engagement, basic competencies and creativity. The results from various case studies show that an innovative and relevant curriculum can create a conducive learning environment and motivate students to continue developing.